On Optimization of “Interval” and “Pointwise” Quadrature Formulas for Classes of Monotone Functions - Borodachov, S.V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider the problem of optimization of “interval” quadrature formulas (in different statements) on the class of monotone functions defined on an interval and the problem of optimization of cubature formulas with fixed knots on classes of functions defined on a d-dimensional cube, d = 2, 3,..., and monotonically nondecreasing with respect to each variable.